Nanopartículas de Fe3O4 funcionalizadas e nanocompósitos de base epóxi - Lima, Bruno Henrique Ramos de (Universidade Federal de São Carlos, 2015)
The use of metal oxide nanoparticles in nanocomposite has provided new and interesting properties and is one of the most promising areas in composites. Compatibility between these nanoparticles and polymer matrix is the most critical fator on development of these materials. In this context, this thesis project has focused on study of synthesis and functionalization of magnetite nanoparticles (Fe3O4) aiming its incorporation into bisphenol A based diglycidyl ether based to produce nanocomposites with very high compatibility between dispersed and matrix phases. Synthesis and functionalization of nanoparticles were performed in a single step by thermodecomposition of iron (III) acetylacetonate in poly (1,4- butanediol) with molar weight 1000, which served both as a solvent for the reaction as a source of molecules for surface functionalization of the nanoparticles. Nanoparticles with an average size of 8,4 nm and with high volume fraction of organic layer were obtained and the synthesis was highly reproducible. The produced nanocomposite exhibited high homogeneity of nanoparticles dispersion and the absence of large agglomerates. The interaction between the nanoparticles and matrix occurred through the chemical reaction between the functional groups of the organic layer and the DGEBA, as was expected, and through intercalation of DGEBA molecules between the molecules from the organic layer, thereby creating a new interphase with unique properties. Due to the high volume fraction of this new phase, the density and modulus of elasticity exhibited behavior that could not be explained by traditional methods. A new approach was used to develop a model that considered this third phase and set more consistently to the experimental data obtained, and showing the domain of this new interphase on the nanocomposite`s properties.
Fe3O4 funtionalized nanoparticles and epoxy based nanocomposites
Keywords: Síntese; Óxidos metálicos; Nanocompósitos; Nanopartículas; Polímeros; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA